An Examination of the Causal Relationship between Budget Deficit and Inflation: a Case Study of Lao PDR - Saysombath, Phouthanouphet (Journal of Social and Development Sciences, 2014)
In this study we try to attempt investigating the dynamic relation between budget deficit and the inflation in the Lao PDR. Using annual data for the period 1980-2010, we apply ARDL cointegration method in conjunction with the structural VAR (SVAR) analysis to provide evidence for both the long and short run dynamics between the variables. We find that there is no long-run relation between the budget deficit and the inflation in Laos. In addition, we also find that there is Granger causality between the budget deficit and the inflation in Laos. The impulse response results in the SVAR model indicate that the budget deficit does not cause inflation but the inflation does cause the budget deficit.